Method for green preparation of straw-based broad-spectrum adsorption material through mechanochemistry
The straw is modified by mechanical force chemistry, increasing the surface area and modifying functional groups, and the problems of low adsorption capacity and poor tolerance of textile printing and dyeing wastewater treatment in the prior art are solved, and the effect of efficient removal of organic dyes and heavy metal ions is achieved.
Patent Information
- Application Number
- CN202510312754.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-17
- Publication Date
- 2025-06-20
AI Technical Summary
The prior art has problems such as low adsorption capacity, poor adsorption of ionic dyes, chemical oxidation method, poor tolerance to high-concentration dyes when treating textile printing and dyeing wastewater, and poor tolerance to high-concentration dyes in biomass adsorbent materials, and low adsorption capacity.
Phosphorus pentoxide and N,N,N-trimethylglycine were connected to the straw by mechanical force chemistry. The straw formed a graded porous structure through high-energy grinding and physical shearing, increasing the specific surface area, and modifying the activated functional groups on the surface to adjust the surface charge to improve adsorption performance.
The adsorption efficiency and multi-pollutant adsorption capacity of straw-based broad-spectrum adsorption materials have been significantly improved, and efficient removal of organic dyes and heavy metal ions has been achieved, production costs and energy consumption have been reduced, and secondary pollution has been avoided.
Smart Images

Figure CN120169317A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of biomass materials / environmental governance. Background Art
[0002] Straw is the main waste in agricultural production, usually referring to the plant residues such as the stalks and leaves remaining after crop harvest. However, there have always been serious problems of waste and low utilization rate of straw resources. Among them, the open stacking or direct burning of straw not only causes waste of resources, but also reduces air quality and pollutes the soil; straw composting and biomass carbonization can use straw as organic fertilizers and soil conditioners, but are limited by problems such as treatment technology and cost; in recent years, studies have shown that straw resources can be efficiently converted into renewable energy through various technical routes such as biomass granulation and fuelization, but the labor costs and investment in technical equipment of related industries are relatively large, and the investment return period is long. All these reasons result in a relatively low utilization rate of straw resources.
[0003] In the fields of textile printing and dyeing, leather processing and papermaking industries, organic dyes are key functional chemicals. However, about 10% - 15% of synthetic dyes in the existing industrial system enter the ecological environment system through production wastewater, forming organic pollutants with persistent pollution characteristics. More seriously, with the large-scale expansion of the global textile industry, the total discharge of printing and dyeing wastewater shows a significant growth trend. Such wastewater constitutes a complex chemical system, and its pollutant spectrum covers various pollutants such as organic dyes, dye derivatives, and heavy metal ions, which has become a key difficult problem in environmental governance. And there are significant technical bottlenecks in the current pollution treatment technology system: the physical adsorption method has a low adsorption capacity due to the low specific surface area characteristics (1 m 2 / g - 10 m 2 / g) of traditional adsorbents such as biomass, and has poor adsorption performance for ionic dyes; although the chemical oxidation method can degrade some dye molecules, it is easy to produce halogenated by-products, causing secondary pollution; the biological treatment method has poor tolerance to high-concentration dyes. In addition, the original pore structure of biomass adsorption materials is blocked and the surface functional groups are scarce, and the adsorption capacity for organic dyes and heavy metal ions is generally low. And there are a large number of toxic and harmful solvents used in the biomass modification process, the production process is complex, the post-treatment process is cumbersome, and the reaction process requires high temperature and high pressure conditions. Based on this, using biomass as the main raw material and constructing a new type of environmental functional material with high specific surface area, controllable surface chemical properties and broad-spectrum adsorption efficiency through molecular design has become the key technical breakthrough direction for realizing the deep purification and resource utilization of industrial wastewater. Summary of the Invention
[0004] The present invention aims to solve the problems of low adsorption capacity and poor adsorption performance for ionic dyes in the existing physical adsorption method, secondary pollution caused by by-products in the chemical oxidation method, and poor tolerance to high-concentration dyes in the biological treatment method; to solve the problems of blocked original pore structure and lack of surface functional groups in the existing biomass adsorption materials, low adsorption capacity for organic dyes and heavy metal ions, and the use of toxic and harmful solvents, complex production processes, cumbersome post-treatment processes and high-temperature and high-pressure conditions in the biomass modification process; and further provide a method for green preparation of straw-based broad-spectrum adsorption materials by mechanochemistry, introducing the mechanochemical catalysis process into the modification of the whole components of straw, inducing ultrafine pulverization of straw (particle size < 10 μm) and breaking of surface chemical bonds through physical force fields such as ball milling and shearing, increasing the specific surface area of straw, exposing more adsorption active sites, and modifying and activating functional groups on the surface of straw, and improving the adsorption performance of straw-based broad-spectrum adsorption materials for organic dyes and heavy metal ions by regulating the surface charge (pH responsiveness).
[0005] A method for green preparation of straw-based broad-spectrum adsorption materials by mechanochemistry, which is carried out according to the following steps:
[0006] I. At normal temperature and pressure, phosphorus pentoxide, N,N,N-trimethylglycine and straw are mixed evenly to obtain a mixture, and then the mixture is subjected to high-energy grinding to obtain a crude product;
[0007] II. The crude product and deionized water are stirred evenly, then the pH is adjusted to 2-14 and stirring is continued. After stirring, centrifugal separation, drying and grinding into powder are carried out in sequence to obtain the straw-based broad-spectrum adsorption material.
[0008] The beneficial effects of the present invention are as follows:
[0009] (1) The present invention uses the mechanochemical method to graft phosphorus pentoxide and N,N,N-trimethylglycine onto straw to prepare a straw adsorption material with surface ion modification, which can improve the positive and negative charges on the surface of straw to directionally adsorb ionic organic dyes and heavy metal ions. At the same time, the specific surface area of the straw modified by mechanochemistry is increased by 200% compared with that of the straw only broken by ordinary physical means. After mechanochemical modification, a large number of hydroxyl (-OH) and carboxyl (-COOH) functional groups are exposed on the surface of straw, and phosphate groups and quaternary ammonium salts are introduced on the surface of straw. When the straw-based broad-spectrum adsorption material (NPK1) is adjusted to be alkaline, the equilibrium adsorption capacities for ionic dyes crystal violet (CV) and methylene blue (MB) can reach 140.87 mg / g and 152.81 mg / g respectively, and the removal rate for heavy metal ions (Cu 2+ ) can reach 98.7%. The mechanochemical method endows the material with better adsorption efficiency and multi-pollutant adsorption ability, and has great application potential in improving the adsorption performance of biomass.
[0010] (2) The straw-based broad-spectrum adsorption material of the present invention uses high-energy grinding and physical shearing to form a hierarchical porous structure (micropores + mesopores) on the surface of the straw, changing the scale of the straw particles to the micron level (1 - 10 μm), which solves the problems of difficult modification processing and utilization of straw materials.
[0011] (3) The straw-based broad-spectrum adsorption material of the present invention adopts a solid-solid reaction, reducing the use of toxic and harmful solvents, avoiding environmental pollution during the production process, and also reducing the cost of material manufacturing.
[0012] (4) The straw-based broad-spectrum adsorption material of the present invention can avoid production environments such as high temperature and high pressure, reduce energy consumption, and also avoid potential safety hazards of combustion and explosion.
[0013] (5) The straw-based broad-spectrum adsorption material of the present invention has excellent adsorption efficiency, and the adsorption equilibrium time is shortened to within 2 h (traditional biomass requires 4 h - 6 h). By regulating the acidity and alkalinity (pH = 2 - 14) of the straw-based broad-spectrum adsorption material, a significant improvement in adsorption performance can be achieved.
[0014] (6) The straw-based broad-spectrum adsorption material of the present invention has good high-concentration dye tolerance. In the range of CV concentration from 30 mg / L to 100 mg / L, the adsorption rate of the straw-based broad-spectrum adsorption material always remains at 97% - 98%, without a significant decrease as the concentration increases, breaking through the bottleneck of the sharp drop in efficiency of traditional adsorbents at high concentrations.
[0015] (7) The straw-based broad-spectrum adsorption material of the present invention has excellent green economy. The raw material used is waste straw, and the cost is significantly lower than that of activated carbon. In addition, the waste adsorbent can be incinerated (heavy metals in the ash can be recycled) or naturally degraded, without the risk of secondary pollution.
[0016] (8) The straw-based broad-spectrum adsorption material of the present invention has good environmental benefits and social value. The modified straw adsorbent can treat a large amount of low-concentration dye and heavy metal wastewater, reducing the generation of wastewater sludge; promoting the resource utilization of agricultural waste, greatly reducing CO2 emissions. In addition, the preparation method of this material is simple, the operation difficulty is low, and the production cycle is short, having good industrial application prospects. Description of the Drawings
[0017] Figure 1 Absorbance standard curves of standard gradient concentration solutions of CV, MB, and Cu 2+ a is CV, b is MB, and c is Cu 2+ ;
[0018] Figure 2 Adsorption test results of the straw-based broad-spectrum adsorption materials (NPK1, NPK2, NPK3) prepared in Examples 1 - 3 for MB;
[0019] Figure 3 Adsorption test results of straw-based broad-spectrum adsorbents (NPK1, NPK2, NPK3) prepared in Examples 1 to 3 for MB at dosages of 0.01 g, 0.03 g, and 0.05 g;
[0020] Figure 4 Isothermal adsorption test results of straw-based broad-spectrum adsorbent (NPK1) prepared in Example 1 for MB and CV from 1 h to 8 h;
[0021] Figure 5 Ultraviolet adsorption test results of straw-based broad-spectrum adsorbent (NPK1) prepared in Example 1 for CV (30 mg / L, 40 mg / L, 50 mg / L, 60 mg / L, 70 mg / L, 80 mg / L, 90 mg / L, 100 mg / L);
[0022] Figure 6 Atomic absorption spectrometry test results of straw-based broad-spectrum adsorbent (NPK1) prepared in Example 1 for Cu at dosages of 0.03 g, 0.05 g, and 0.1 g 2+ ;
[0023] Figure 7 Nitrogen desorption and desorption diagram (N2-TPD) of straw-based broad-spectrum adsorbent (NPK1) prepared in Example 1 and MS, where a is NPK1 and b is MS;
[0024] Figure 8 BET linear equation diagram of straw-based broad-spectrum adsorbent (NPK1) prepared in Example 1 and MS;
[0025] Figure 9 SEM test diagram of straw-based broad-spectrum adsorbent (NPK1) prepared in Example 1 and MS at a scale of 50 μm, where a is NPK1 and b is MS;
[0026] Figure 10 Thermal stability test diagram of straw-based broad-spectrum adsorbent (NPK1) prepared in Example 1 and MS, where a is NPK1 and b is MS;
[0027] Figure 11 FTIR test diagram of straw-based broad-spectrum adsorbent (NPK1) prepared in Example 1 and MS. Detailed implementation manners
[0028] Detailed implementation manner 1: A method for mechanically chemically and greenly preparing a straw-based broad-spectrum adsorbent in this implementation manner is carried out according to the following steps:
[0029] 1. At normal temperature and pressure, mix phosphorus pentoxide, N,N,N-trimethylglycine and straw evenly to obtain a mixture, and then subject the mixture to high-energy grinding to obtain a crude product;
[0030] 2. Stir the crude product and deionized water evenly, then adjust the pH to 2-14 and continue stirring. After stirring, perform centrifugal separation, drying and grinding into powder in sequence to obtain a straw-based broad-spectrum adsorption material.
[0031] The chemical formula of the phosphorus pentoxide described in this specific embodiment is The chemical formula of the N,N,N-trimethylglycine described is
[0032] This specific embodiment constructs a new type of environmental functional material with high specific surface area, controllable surface chemical properties and broad-spectrum adsorption efficiency through molecular design. Using mechanochemical technology to carry out high-energy impact reaction, surface double-ion modification and physical and chemical modification on biomass materials, the reaction materials are prepared into ultrafine particles with a particle size up to the micron scale, effectively solving the problems of difficult modification and low utilization rate of current straw resources.
[0033] Compared with traditional chemical modification, this technology does not require organic solvents, significantly reduces energy consumption, and the modified straw adsorbent is biodegradable, avoiding secondary pollution. It realizes the functional conversion of all components of straw without high-temperature and high-pressure reaction conditions, meeting the concept of green chemistry. It not only avoids pollution to the environment caused by straw modification, but also effectively avoids potential combustion and explosion hazards. At the same time, it can be widely used and industrially produced on a large scale, and has great potential in the treatment of organic dyes and heavy metal pollution.
[0034] The beneficial effects of this embodiment are:
[0035] (1) This embodiment uses the mechanochemical method to graft phosphorus pentoxide and N,N,N-trimethylglycine onto straw, and prepares a straw adsorption material with surface ion modification. The positive and negative charges on the straw surface are improved to be able to directionally adsorb ionic organic dyes and heavy metal ions. At the same time, the specific surface area of the straw modified by mechanochemistry is increased by 200% compared with that of the straw only broken by ordinary physical means. After mechanochemical modification, a large number of hydroxyl (-OH) and carboxyl (-COOH) functional groups are exposed on the straw surface. At the same time, phosphate groups and quaternary ammonium salts are introduced on the straw surface. When adjusting the straw-based broad-spectrum adsorption material (NPK1) to be alkaline, the equilibrium adsorption capacities for the ionic dyes crystal violet (CV) and methylene blue (MB) can reach 140.87 mg / g and 152.81 mg / g respectively, and for heavy metal ions (Cu 2+) The removal rate can reach 98.7%. The mechanochemical method endows the material with better adsorption efficiency and the ability to adsorb multiple pollutants, and has great application potential in improving the adsorption performance of biomass.
[0036] (2) The straw-based broad-spectrum adsorption material of this embodiment uses high-energy grinding and physical shearing to form a hierarchical porous structure (micropores + mesopores) on the surface of the straw, and changes the scale of the straw particles to the micron level (1 - 10 μm), solving the problems of difficult modification processing and utilization of straw materials.
[0037] (3) The straw-based broad-spectrum adsorption material of this embodiment adopts a solid-solid reaction, reducing the use of toxic and harmful solvents, avoiding environmental pollution during the production process, and also reducing the cost of material manufacturing.
[0038] (4) The straw-based broad-spectrum adsorption material of this embodiment can avoid production environments such as high temperature and high pressure, reduce energy consumption, and also avoid potential safety hazards of combustion and explosion.
[0039] (5) The straw-based broad-spectrum adsorption material of this embodiment has excellent adsorption efficiency, and the adsorption equilibrium time is shortened to within 2 h (traditional biomass requires 4 h - 6 h). By regulating the acidity and alkalinity (pH = 2 - 14) of the straw-based broad-spectrum adsorption material, a substantial improvement in adsorption performance can be achieved.
[0040] (6) The straw-based broad-spectrum adsorption material of this embodiment has good high-concentration dye tolerance. In the range of CV concentration from 30 mg / L to 100 mg / L, the adsorption rate of the straw-based broad-spectrum adsorption material always remains at 97% - 98%, without a significant decrease with the increase in concentration, breaking through the bottleneck of the sharp drop in efficiency of traditional adsorbents at high concentrations.
[0041] (7) The straw-based broad-spectrum adsorption material of this embodiment has excellent green economy. The raw material used is waste straw, and the cost is significantly lower than that of activated carbon. In addition, the waste adsorbent can be incinerated (heavy metals in the ash can be recycled) or naturally degraded, without the risk of secondary pollution.
[0042] (8) The straw-based broad-spectrum adsorption material of this embodiment has good environmental benefits and social value. The modified straw adsorbent can treat a large amount of low-concentration dye and heavy metal wastewater, reducing the generation of wastewater sludge; promoting the resource utilization of agricultural waste and greatly reducing CO2 emissions. In addition, the preparation method of this material is simple, the operation difficulty is low, and the production cycle is short, with good industrial application prospects.
[0043] Specific Embodiment 2: The difference between this embodiment and Specific Embodiment 1 is that the straw mentioned in Step 1 is soybean straw, rice straw, rapeseed straw, corn straw, corn cob, rice husk or wheat straw. Others are the same as Specific Embodiment 1.
[0044] Specific Embodiment 3: The difference between this embodiment and one of Specific Embodiments 1 or 2 is that: the particle size of the straw described in Step 1 is 5 mesh to 800 mesh. Others are the same as Specific Embodiment 1 or 2.
[0045] Specific Embodiment 4: The difference between this embodiment and one of Specific Embodiments 1 to 3 is that: the straw described in Step 1 is pretreated straw, and the pretreatment is carried out according to the following steps: washing and filtering with deionized water, and repeating the washing and filtering 1 to 5 times, and then under the condition of a temperature of 50°C to 80°C, vacuum drying for 12h to 24h. Others are the same as Specific Embodiment 3.
[0046] Specific Embodiment 5: The difference between this embodiment and one of Specific Embodiments 1 to 4 is that: the molar ratio of the mass of the straw described in Step 1 to phosphorus pentoxide is 4g:(3.5 to 7.1) mmol. Others are the same as Specific Embodiments 1 to 4.
[0047] Specific Embodiment 6: The difference between this embodiment and one of Specific Embodiments 1 to 5 is that: the molar ratio of phosphorus pentoxide to N,N,N-trimethylglycine described in Step 1 is 1:(1 to 2). Others are the same as Specific Embodiments 1 to 5.
[0048] Specific Embodiment 7: The difference between this embodiment and one of Specific Embodiments 1 to 6 is that: the high-energy grinding described in Step 1 is specifically carried out according to the following steps: using a planetary ball mill or a reciprocating mill, under the conditions of a vibration frequency of 15Hz to 30Hz and a ball-to-material mass ratio of (10 to 32):1, high-energy grinding for 1h to 12h; and during the high-energy grinding process, the rotation direction of the ball mill tank is changed every 1h of grinding, and steel balls with a diameter of 5mm to 20mm are used as grinding balls. Others are the same as Specific Embodiments 1 to 6.
[0049] Specific Embodiment 8: The difference between this embodiment and one of Specific Embodiments 1 to 7 is that: the mass ratio of the crude product described in Step 2 to the volume of deionized water is 1g:(10 to 100) mL. Others are the same as Specific Embodiments 1 to 7.
[0050] Specific Embodiment 9: The difference between this embodiment and one of Specific Embodiments 1 to 8 is that: in Step 2, the pH is adjusted to 2 to 14, and under the condition of a rotation speed of 100rpm to 1000rpm, stirring is continued for 1h to 12h. Others are the same as Specific Embodiments 1 to 8.
[0051] Specific Embodiment Ten: The difference between this embodiment and any one of Specific Embodiments One to Nine is as follows: For the centrifugal separation, drying, and grinding into powder described in Step 2, the following steps are specifically carried out: Centrifugal separation is carried out under the condition of a rotational speed of 10,000 rpm to 13,000 rpm, then drying is carried out for 12 h to 24 h under the condition of a temperature of 50 °C to 80 °C, and finally manual grinding is carried out for 10 min to 120 min. Others are the same as Specific Embodiments One to Nine.
[0052] The following examples are used to verify the beneficial effects of the present invention:
[0053] Example 1:
[0054] A method for mechanically chemically preparing a straw-based broad-spectrum adsorbent in a green manner, which is carried out according to the following steps:
[0055] I. At normal temperature and pressure, 7.04 mmol of phosphorus pentoxide (P2O5), 8.55 mmol of N,N,N-trimethylglycine (Betaine), and 4 g of straw are mixed evenly to obtain a mixture. Then, using a planetary ball mill, under the conditions of a vibration frequency of 30 Hz and a ball-to-material mass ratio of 10.67:1, the mixture is subjected to high-energy grinding for 2 h to obtain a crude product;
[0056] During the high-energy grinding process, the rotation direction of the ball mill tank is changed every 1 h. Steel balls with a diameter of 20 mm are used as grinding balls, and the number is 2; The material of the ball mill tank used is 504 hard steel, and the volume of the ball mill tank is 100 mL;
[0057] The straw mentioned above is soybean straw;
[0058] The particle size of the straw is 5 mesh;
[0059] II. The crude product and deionized water are stirred evenly, then the pH is adjusted to 12 using a 0.1 M potassium hydroxide solution, and under the condition of a rotational speed of 1000 rpm, stirring is continued for 12 h. After stirring, centrifugal separation, drying, and grinding into powder are carried out in sequence to obtain an alkaline straw-based broad-spectrum adsorbent, named NPK1;
[0060] The mass ratio of the crude product to the volume of deionized water is 1 g:50 mL.
[0061] The straw mentioned in Step I is pretreated straw, and the pretreatment is carried out according to the following steps: Wash and filter with deionized water, and repeat the washing and filtering 3 times, then under the condition of a temperature of 50 °C, vacuum drying is carried out for 12 h.
[0062] The centrifugal separation, drying, and grinding into powder described in Step 2 are specifically carried out according to the following steps: Centrifugal separation is carried out at a rotational speed of 12000 rpm, then drying is carried out for 12 h at a temperature of 50 °C, and finally manual grinding is carried out for 30 min.
[0063] The planetary ball mill described in Step 1 has a model number of QM-3SP04.
[0064] Example 2: The difference between this example and Example 1 is that in Step 2, the crude product and deionized water are stirred evenly, the pH is adjusted to 7 using a potassium hydroxide solution with a concentration of 0.1 M, and stirring is continued for 12 h at a rotational speed of 1000 rpm. After stirring, centrifugal separation, drying, and grinding into powder are carried out in sequence to obtain a neutral straw-based broad-spectrum adsorbent material named NPK2. Others are the same as in Example 1.
[0065] Example 3: The difference between this example and Example 1 is that in Step 2, the crude product and deionized water are stirred evenly, the pH is adjusted to 2 using a potassium hydroxide solution with a concentration of 0.1 M, and stirring is continued for 12 h at a rotational speed of 1000 rpm. After stirring, centrifugal separation, drying, and grinding into powder are carried out in sequence to obtain an acidic straw-based broad-spectrum adsorbent material named NPK3. Others are the same as in Example 1.
[0066] Test Example 1: Determination of the standard gradient concentration curves of CV, MB dyes, and Cu 2+ : CV is a triphenylmethane-based basic dye, and its molecular structure has characteristic absorption peaks in the visible light region (500 nm - 600 nm). MB is a phenothiazine-based cationic dye, and its conjugated structure shows characteristic absorption peaks in the visible light region (600 nm - 700 nm). By measuring the absorbance of two series of standard solutions of the dyes at their maximum absorption wavelengths (CV: 584 nm, MB: 665 nm), with the concentration (C, mg / L) as the abscissa and the absorbance (ABS) as the ordinate, a linear relationship between the absorbance (ABS) and the concentration (C) is established. Copper ions (Cu 2+ ) have characteristic absorption peaks (wavelength 324.8 nm) in atomic absorption spectroscopy (AAS). By atomizing the copper-containing standard solution and measuring the absorbance at a specific wavelength after atomization, a linear relationship between the absorbance (A) and the concentration (C) is established. The absorbance test data of the standard gradient concentration solutions of the two dyes and Cu 2+ are shown in Table 1. Take the CV standard gradient solution (6 mg / L - 10 mg / L), the MB standard gradient solution (1 mg / L - 4 mg / L), and the Cu 2+ standard gradient solution (0.25 mg / L - 5 mg / L) to plot the standard curve and calculate the linear regression equation to provide a basis for subsequent sample quantitative analysis. The calculation results are as Figure 1 shown.Figure 1 For CV, MB and Cu 2+ Absorbance standard curve of standard gradient concentration solutions, where a is CV, b is MB, and c is Cu 2+ 。
[0067] Table 1 CV, MB and Cu 2+ Absorbance test data of standard gradient concentration solutions
[0068]
[0069] Test Example 2: Influence of the acidity and alkalinity of straw-based broad-spectrum adsorbent materials on adsorption performance: In this test example, by regulating the pH of the straw-based broad-spectrum adsorbent materials, the influence of the acidity and alkalinity of the straw-based broad-spectrum adsorbent materials on adsorption performance was revealed. Based on the results of preliminary pre-experiments, the straw-based broad-spectrum adsorbent materials had good adsorption effects on both organic dyes and heavy metal ions. Therefore, in this test experiment, MB dye was used for analysis. A 50 mL simulated industrial organic dye wastewater system with an initial concentration of 50 mg / L of MB was prepared. 0.01 g of the straw-based broad-spectrum adsorbent materials (NPK1, NPK2, NPK3) prepared in Examples 1 to 3 were added to 50 mL of the MB solution with an initial concentration of 50 mg / L respectively. Three parallel samples were set for each group of samples. An adsorption equilibrium experiment was carried out for 24 h under the conditions of constant temperature (25 ± 1 °C) and an oscillation rate of 200 rpm. Solid-liquid separation was carried out by gravity sedimentation coupled with filtration through a 0.45 μm microporous membrane. The residual MB concentration was measured using a UV-visible spectrophotometer (UV-Vis, 665 nm). Accordingly, the pH-dependent adsorption capacity (mg / g) and the organic dye adsorption rate (%) were calculated to analyze the influence of the acidity and alkalinity of the ion-modified straw materials on the adsorption effect.
[0070] Figure 2 Graph of the adsorption test results of the straw-based broad-spectrum adsorbent materials (NPK1, NPK2, NPK3) prepared in Examples 1 to 3 for MB; As can be seen from the graph, the adsorption performance of the straw-based broad-spectrum adsorbent materials showed significant pH dependence. Experimental data showed that: the equilibrium adsorption capacity (q e ) of the NPK3 material was approximately 28.2 mg / g, and the adsorption rate (η) was approximately 18.8%. The adsorption efficiency was relatively low, which might be attributed to the protonation of surface functional groups (such as hydroxyl groups and carboxyl groups) on the material surface in an acidic environment, resulting in a relatively high surface positive charge density and electrostatic repulsion with the positively charged MB cations, thus inhibiting adsorption. In addition, high-concentration H +It may occupy the active sites on the material surface through ion exchange, further weakening the adsorption capacity for MB; the adsorption capacity of NPK2 material for MB slightly increases to about 39.25 mg / g, and η is about 26.1%. As the pH of the material increases, the negative charge density on the material surface increases, and the electrostatic attraction with MB cations is enhanced, promoting adsorption; the adsorption capacity of NPK1 material reaches the maximum value (about 131.25 mg / g), and the adsorption rate reaches 87.5%, indicating that the material has the optimal adsorption performance in an environment with enhanced alkalinity. Under the condition of enhanced alkalinity, the negative charge density on the surface of the modified straw material further increases, significantly enhancing the electrostatic attraction with MB cations. It is worth noting that as the pH of the straw material increases, the adsorption capacity shows a monotonically increasing trend (the blue data points are fitted to the orange curve), indicating that the adsorption process of the material for MB is significantly regulated by pH, and the alkaline environment is more conducive to exerting its adsorption potential.
[0071] Test Example 3: Influence of the feeding amount on the adsorption performance of the straw-based broad-spectrum adsorption material: Prepare 50 mL of simulated industrial organic dye wastewater of MB with an initial concentration of 30 mg / L, and gradually add 0.01 g, 0.03 g, and 0.05 g of the straw-based broad-spectrum adsorption materials NPK1, NPK2, and NPK3 prepared in Examples 1 to 3 to the MB solution. To ensure the reliability of the experiment, three parallel controls are added for each sample. Dynamic adsorption is carried out for 24 h under the conditions of constant temperature (25 ± 1 °C) and an oscillation rate of 200 rpm. After adsorption equilibrium, solid-liquid separation is achieved through the combined technology of gravity sedimentation - membrane filtration (0.45 μm microporous membrane), and the residual dye concentration is quantitatively determined by ultraviolet-visible spectrophotometry (UV-Vis, 665 nm). Based on this, the adsorption rate under different feeding amounts is calculated to explore the adsorption effect of the straw-based broad-spectrum adsorption material on dyes under different feeding amounts.
[0072] Figure 3Adsorption test results of the straw-based broad-spectrum adsorbents (NPK1, NPK2, NPK3) prepared in Examples 1 to 3 for MB at the feeding amounts of 0.01 g, 0.03 g, and 0.05 g; It can be analyzed that the adsorption rates of the NPK3 material for MB at the three dosages of 0.01 g, 0.03 g, and 0.05 g are relatively low, being 18.8%, 30.3%, and 54.8% respectively. This is because NPK3 is acidic as a whole, and the electrostatic repulsion between the material surface and the MB cations is enhanced, thus inhibiting the adsorption effect. As the alkalinity of the material increases, the adsorption rate increases significantly. The adsorption rates of NPK2 for MB at the feed amounts of 0.01 g, 0.03 g, and 0.05 g are increased to 26.1%, 81.1%, and 92.9% respectively, indicating that the surface charge state tends to be balanced when the material is neutral, which is conducive to the adsorption of MB molecules. The adsorption rates of NPK1 reach the maximum values at the feed amounts of 0.01 g, 0.03 g, and 0.05 g, being 87.5%, 96.9%, and 97.9% respectively. This is attributed to the fact that when the alkalinity of the material increases, the electrostatic attraction between the negatively charged functional groups (such as carboxyl and hydroxyl groups) and the MB cations is enhanced, significantly improving the adsorption efficiency. In addition, as the dosage of the straw-based broad-spectrum adsorbent increases (from 0.01 g to 0.05 g), the adsorption rate of the material for MB increases significantly. For example, the adsorption rate of NPK2 at the dosage of 0.05 g is increased by 66.8% compared with that at 0.01 g. This shows that increasing the dosage of the straw-based broad-spectrum adsorbent can provide more active adsorption sites, thereby enhancing the adsorption capacity for MB. The NPK1, NPK2, and NPK3 at the dosage of 0.05 g all show the optimal adsorption performance, further confirming that the adsorption performance of the straw-based broad-spectrum adsorbent is continuously enhanced as the feeding amount increases.
[0073] Test Example 4: Influence of adsorption time on the adsorption performance of the straw-based broad-spectrum adsorbent: Measure 500 mL of CV and MB simulated industrial organic dye wastewater with an initial concentration of 30 mg / L respectively. According to the above experimental test results, test NPK1, uniformly control the adsorbent dosage to be 0.084 g, and conduct a time gradient experiment (1 h to 8 h) under the conditions of constant temperature (25 ± 1 °C) and oscillation rate of 200 rpm. Set triple parallel samples at each time node to control the experimental error. After the adsorption process is terminated, phase separation is achieved by the combined technology of gravity sedimentation and membrane filtration, and the UV-Vis spectrophotometry (UV-Vis, CV: 584 nm, MB: 665 nm) is used to accurately measure the residual CV and MB concentrations in the liquid phase, and calculate q e , to study the influence of different adsorption times on the adsorption performance of the straw-based broad-spectrum adsorbent.
[0074] Figure 4Isotherm adsorption test results of the straw-based broad-spectrum adsorption material (NPK1) prepared in Example 1 for MB and CV from 1 h to 8 h; the test results show that the adsorption behavior of NPK1 for the two dyes has significant time dependence. In the rapid adsorption stage (0 h - 2 h): the adsorption amounts of MB and CV increase rapidly within the initial 2 hours, reaching 85.57% and 78.89% of the equilibrium adsorption amounts respectively. The high adsorption rate in this stage is attributed to the strong electrostatic attraction and π-π interaction between the abundant active adsorption sites (oxygen- and nitrogen-containing functional groups introduced by NPK) on the surface of the modified straw material and the dye molecules. In the dynamic equilibrium stage (2 h - 8 h): as time prolongs, the adsorption rate decreases significantly and the adsorption amount tends to be stable. And since the difference between the adsorption amount of CV after 2 h and the equilibrium adsorption amount is not large, and it can reach a high adsorption efficiency of 80% within 2 h, the adsorption equilibrium time can be considered to be shortened to within 2 h. The equilibrium adsorption amounts of MB and CV are stabilized at about 152.81 mg / g and 140.87 mg / g respectively, indicating that the adsorption sites on the material surface are gradually saturated and the adsorption process enters dynamic equilibrium. In addition, the equilibrium adsorption amount of MB is slightly higher than that of CV, which may be related to the molecular structure differences of the two dyes. The planar conjugated structure of MB is more likely to form π-π stacking with the functional groups on the surface of the modified material, while the multiple methyl groups in the CV molecule may cause steric hindrance effects and reduce its adsorption efficiency. To sum up, the straw-based broad-spectrum adsorption material shows rapid adsorption characteristics for both MB and CV, reaching about 80% of the equilibrium adsorption amount within 2 hours, indicating its potential for rapid response in actual wastewater treatment. At the same time, the equilibrium adsorption amounts of the adsorption material for the two organic dyes are both higher than 140 mg / g and the adsorption capacity has no significant attenuation, proving its structural stability and broad-spectrum applicability to organic dye wastewater.
[0075] Test Example 5: Effect of adsorption concentration on the adsorption performance of the straw-based broad-spectrum adsorption material: Prepare 50 mL of CV simulated industrial organic dye wastewater with initial concentrations of 30 mg / L, 40 mg / L, 50 mg / L, 60 mg / L, 70 mg / L, 80 mg / L, 90 mg / L, and 100 mg / L. Add 0.05 g of the straw-based broad-spectrum adsorption material NPK1 to the CV solution. To ensure the reliability of the experiment, three parallel controls are added to each sample. Carry out 24-hour dynamic adsorption under the conditions of constant temperature (25 ± 1 °C) and oscillation rate of 200 rpm. After adsorption equilibrium, solid-liquid separation is achieved by the combined technology of gravity sedimentation - membrane filtration (0.45 μm microporous membrane). The residual dye concentration is quantitatively determined by ultraviolet-visible spectrophotometry (UV-Vis, 584 nm). Based on this, the adsorption rate at different concentrations is calculated to explore the effect of adsorption concentration on the adsorption performance of the straw-based broad-spectrum adsorption material.
[0076] Figure 5UV adsorption test results of the straw-based broad-spectrum adsorption material (NPK1) prepared in Example 1 for CV (30 mg / L, 40 mg / L, 50 mg / L, 60 mg / L, 70 mg / L, 80 mg / L, 90 mg / L, 100 mg / L); in the range of CV concentration from 30 mg / L to 100 mg / L, the adsorption rate of NPK1 always remained between 97% and 98%. Among them, when the CV concentration was 30 mg / L, the adsorption rate of NPK1 reached 97.23%. When the concentration doubled to 60 mg / L, the adsorption rate of NPK1 slightly increased to 98.15%. When the highest concentration reached 100 mg / L, the adsorption rate reached 98.34%. The adsorption rate of NPK1 did not show a significant decrease with the increase in concentration. At the same time, the adsorption rate slightly increased with the increase in the CV dye concentration, indicating that the binding ability between the surface active sites of the material and CV molecules is extremely strong, and high-efficiency adsorption can still be maintained even at high concentrations. Different from conventional adsorption materials, this material did not show the phenomenon of adsorption site saturation at high concentration CV (100 mg / L), indicating that it has rich active sites and multiple adsorption paths. In addition, the characteristic that the adsorption rate hardly changes with concentration indicates that the hierarchical pore structure (micropores-mesopores) and functional group distribution of the material can effectively disperse the CV molecule load and avoid the efficiency decay caused by local site oversaturation. The NPK and mechanochemical synergistically modified straw material has stable performance in the range of 30 mg / L to 100 mg / L, breaking through the bottleneck of the sharp drop in efficiency of traditional adsorbents at high concentrations.
[0077] Test Example 6: Adsorption effect of straw-based broad-spectrum adsorption material on heavy metal ions: The adsorption performance of the modified straw material on heavy metal ions was evaluated through an isothermal adsorption experiment system. A 50 mL copper ion simulated industrial organic dye wastewater system with an initial concentration of 50 mg / L (using CuSO4 as the copper source) was prepared, and 0.03 g, 0.05 g, and 0.1 g of the straw-based broad-spectrum adsorption material (NPK1) were added in gradients. Three parallel control samples were added to each sample. A 24-hour dynamic adsorption equilibrium experiment was carried out under the conditions of constant temperature (25 ± 1 °C) and oscillation rate of 200 rpm. After adsorption, solid-liquid separation was achieved by combining gravity sedimentation and a microporous membrane (0.45 μm). The residual copper ion concentration in the liquid phase was accurately measured by flame atomic absorption spectrometry (AAS, λ = 324.8 nm), and the adsorption rate was calculated accordingly to study the adsorption effect of the adsorption material on heavy metal ions.
[0078] Figure 6 Atomic absorption spectrometry test results of the straw-based broad-spectrum adsorption material (NPK1) prepared in Example 1 at dosages of 0.03 g, 0.05 g, and 0.1 g for Cu 2+ ; in the range of sample amount from 0.03 g to 0.1 g, the modified straw material for Cu 2 +The adsorption rate is always higher than 98%, and shows a slight upward trend with the increase of the sample amount (98.7% at 0.03 g and 99.5% at 0.1 g). This indicates that the surface active sites of the material have excellent adsorption ability for Cu 2+ , and can achieve efficient adsorption even at low dosing amounts. In addition, the adsorption rate approaches 100% with the increase of the sample amount, indicating that the material can still meet the high-concentration Cu 2+ wastewater treatment requirements at lower dosing amounts, greatly reducing the material usage cost, providing a green and sustainable solution for heavy metal pollution control, and having the economy and efficiency for practical applications.
[0079] Test Example Seven: (N2-TPD) Test conditions: In the sample pretreatment stage, accurately measure 1.5 g of the solid powder sample and place it in a forced-air drying oven for high-temperature (90 °C) drying treatment for 24 h to ensure that the sample is dried sufficiently. The sample is subjected to a gas-phase desorption experiment at liquid nitrogen temperature (77 K). Nitrogen is used as the probe gas in the experiment. The scanning range is 5° to 65°, the scanning speed is set at 0.05° / s, and the absolute pressure of the experimental system vacuum is 10 -6 mmHg, and the relative pressure (at liquid nitrogen temperature) is 10 -9 . The experiment lasts for 50 h, and data acquisition is carried out in the precise AFSM (automatic correction) mode. Among them, the soybean straw MS treated by ordinary physical shearing and crushing is used as a comparative experiment; the preparation process of MS is as follows: Pretreat the crude soybean straw, wash and filter it with deionized water, and repeat the washing and filtering 3 times. Then, under the condition of a temperature of 50 °C, vacuum dry it for 12 h until the sample reaches a constant weight. Put the dried sample into a grinding jar, and load two 504 steel balls (d = 20 mm) into the jar. Put the sealed grinding jar into a ball mill and grind it for 2 h under the conditions of a frequency of 30 Hz and a ball-to-material mass ratio of 10.67:1. After grinding, take out the sample and seal it for storage, and name it MS. Figure 7 Figure shows the nitrogen desorption isotherms (N2-TPD) of the straw-based broad-spectrum adsorption material (NPK1) prepared in Example 1 and MS. a is NPK1, and b is MS; as can be seen from the figure, the adsorption amounts of the two samples increase gently in the relatively low pressure region (p / p0 < 0.4), conforming to the characteristics of type IV isotherm (IUPAC classification), indicating that the material is mainly dominated by mesoporous structure. The adsorption process can be divided into three stages: low pressure region (p / p0 < 0.1): mainly monolayer adsorption, and the curve rises gently, reflecting the limited micropore filling of the material; middle pressure region (0.4 < p / p0 < 0.8): a steep jump in the adsorption amount appears, corresponding to the capillary condensation phenomenon, indicating the concentrated distribution of mesoporous structure; high pressure region (p / p0 > 0.9): the adsorption amount tends to be saturated, attributed to the macroscopic filling of macropores or particle gaps. NPK1 shows an obvious adsorption sudden increase in the high pressure region (p / p0 > 0.9), and the desorption branch hysteresis loop shows the characteristics of type H3 (Figure 7 -a), presumably originating from the slit-shaped pores formed by the stacking of layered particles, while the MS sample ( Figure 7 -b) The test results are significantly lower than those of NPK1, demonstrating the significant advantages of the mechanochemical and ionic synergistic modification strategy. It should be noted that the desorption curve is not completely closed (residual adsorption amount at p / p0 < 0.3), which may be attributed to the strong adsorption of hydroxyl groups on the material surface or temperature fluctuations during the test.
[0080] Based on the linearization analysis of the BET specific surface area test diagram (abscissa: relative pressure p / p0, ordinate: normalized adsorption amount p / [V a (p0 - p)]), the adsorption characteristics of NPK1 and MS were characterized. Figure 8 BET linear equation diagram of the straw-based broad-spectrum adsorption material (NPK1) and MS prepared in Example 1; as shown in the figure, both samples showed good linearity (R 2 > 0.99) in the range of p / p0 = 0.05 - 0.30, meeting the applicable conditions of the BET theory. Among them, the NPK1 curve is at the bottom and has the smallest slope, indicating that its monolayer adsorption capacity (V m ) is the largest. The specific surface areas of the two materials were calculated by the BET equation, and the specific surface areas and other data results of NPK1 and MS obtained by linear fitting are shown in Table 2. After calculation, its specific surface area (SSA) is 5.5703 m 2 / g, significantly higher than that of MS (2.8557 m 2 / g). This difference is attributed to the directional fragmentation of the fiber structure by mechanochemical action, exposing more cellulose microfibrils and forming hierarchical pores (coexistence of micropores and mesopores). At the same time, the nitrogen, phosphorus, and potassium modification conditions are far superior to ordinary physical shearing and crushing treatments in improving the adsorption performance of straw. The MS sample curve is at the top, and the test results show that simple mechanical crushing can increase the specific surface area, but lack the construction of chemical active sites, resulting in poor adsorption performance of the material.
[0081] Table 2 Specific surface areas and other data results of NPK1 and MS
[0082]
[0083]
[0084] Test Example VIII: SEM Test Conditions: The experimental parameters were set as an acceleration voltage of 5 kV. Before the test, the powder sample was dried and pretreated (in a constant temperature oven at 60 °C - 80 °C for 2 h - 4 h) to eliminate the interference of adsorbed water on the material surface with the test signal. Subsequently, 1 mg - 2 mg of the dried sample was accurately weighed and formed a dispersion system with an appropriate amount of absolute ethanol, and ultrasonic treatment (5 min - 10 min) was carried out to achieve mechanical depolymerization of the particles. The double-sided conductive tape was flatly adhered to the sample stage substrate, and the dispersed sample suspension was aspirated with a fine needle and dropped on the surface of the conductive glue. The sample was left standing at room temperature for 30 min to completely volatilize the solvent. Finally, the weakly adhered particles on the surface of the conductive glue were removed by an ear syringe to reduce the risk of equipment contamination caused by particle migration in a high vacuum environment, and a gold film with a thickness of about 10 nm was sputtered on the surface of the sample by an ion sputtering instrument. Figure 9 SEM test images of the straw-based broad-spectrum adsorbent (NPK1) prepared in Example 1 and MS at a scale of 50 μm. a is NPK1, and b is MS. There are obvious differences in the SEM test results of the two materials. It can be clearly seen from the figure that NPK1 presents a uniformly dispersed micron-scale particle system with an average particle size of 5.3 ± 3.8 μm, while there are still a large number of undissociated straw tissue fragments in the MS sample, and the difference between the two is about 10 times. The NPK1 particles prepared by mechanochemical modification are finer and more dispersed. Since MS was not subjected to mechanochemical activation and only underwent macroscopic fragmentation, most of the straw tissues still aggregated together, resulting in a decrease in reactivity. This indicates that high-energy impact is an indispensable part of the preparation process of the adsorbent in this example, and at the same time verifies the importance of high-energy ball milling. Through the synergistic effect of a high-intensity mechanical shear force field and chemical input, fine crushing treatment of straw-based plant biomass materials can be achieved, and they can be successfully deconstructed into a micron-scale uniformly dispersed particle system. The mechanochemical method optimized the particle size distribution of straw fibers, effectively solved the problems of poor interfacial compatibility and difficult processing and modification caused by the dense structure of traditional straw materials, and provided an innovative solution for the high-value utilization of biomass resources.
[0085] Test Example IX: TG-DTG Test Conditions: The stability of the biosorbent was measured by operating a thermogravimetric / differential thermal analyzer (HCT-3, China, 10 °C / min, N2 flow rate: 50 mL / min). Figure 10 Thermal stability test images of the straw-based broad-spectrum adsorbent (NPK1) prepared in Example 1 and MS. a is NPK1, and b is MS. It can be seen from the figure that the temperature of the maximum weight loss rate of NPK1 is 305.112 °C, which is lower than that of ordinary straw raw materials, indicating that mechanochemical catalysis destroyed the tough structure of the straw and improved the reactivity of the straw. In addition, the mass change of NPK1 before 100 °C is small, indicating that NPK1 has good stability below 100 °C and can cope with temperature changes in a complex external environment.
[0086] Test Example Ten: FTIR Test Conditions: The Nicolet iS50 Fourier Transform Infrared Spectrometer (FTIR) was used to analyze the surface functional groups of the experimental samples. The dried and ground sample powder (about 100 mg) was placed in an agate mortar and ground thoroughly for more than 30 min until the sample particle size was less than 10 μm. Subsequently, the evenly ground sample was carefully transferred to a pressing mold and placed in a tablet press. The pressure was increased to 1 HPa by manual pressing and maintained for about 3 min to prepare a uniform test tablet. The prepared tablet was placed in the Fourier Transform Infrared Spectrometer, and spectral acquisition was carried out under the conditions of a wavenumber range of 500 cm -1 ~4000 cm -1 and a resolution of 2 cm -1 . Figure 11 FTIR test chart of the straw-based broad-spectrum adsorption material (NPK1) and MS prepared in Example 1; It can be seen from the figure that compared with MS, the main absorption peak positions of NPK1 are at 3321 cm -1 , 1604 cm -1 and 1019 cm -1 near the wavenumbers, which correspond to the stretching vibrations of O-H (hydroxyl group) and P-OH respectively; the skeletal vibrations of C=C and -COO - bonds; and the stretching vibrations of C-O-C and P-O-C (phosphate ester). In the NPK1 sample, the functional groups such as O-H, -COO-, and C-O-C are more strongly expressed compared with MS, which indicates that high-energy grinding and impact will make the straw more activated and increase the abundance of oxygen-containing functional groups. At the same time, the appearance of the characteristic peaks of P-OH and P-O-C indicates that P2O5 has been successfully grafted onto the straw. In addition, at the wavenumber of 1513 cm -1 , the characteristic peak of NPK1 is caused by the characteristic absorption of the quaternary ammonium group N + (CH3)3, indicating that Betaine has been successfully grafted onto the straw. During the high-energy grinding and impact process, more active hydroxyl groups on the straw surface are exposed and combined with more charged ions, resulting in an increase in the number of oxygen-containing groups and improving the activity of the straw, proving that the high-energy ball milling method can effectively catalyze and activate crop straw and increase the abundance of surface functional groups of straw.
Claims
1. A method for preparing straw-based broad-spectrum adsorption materials by mechanochemical green method, characterized in that It is carried out in the following steps:
1. At normal temperature and pressure, phosphorus pentoxide, N,N,N-trimethylglycine and straw are uniformly mixed to obtain a mixture, and then the mixture is subjected to high-energy grinding to obtain a crude product; 2. The crude product and deionized water are stirred evenly, and then the pH is adjusted to 2-14 and stirring is continued. After stirring, centrifugal separation, drying and grinding into powder are carried out in sequence to obtain a straw-based broad-spectrum adsorption material.
2. The method for preparing straw-based broad-spectrum adsorption materials by mechanochemical green method according to claim 1 is characterized in that The straw described in step 1 is soybean straw, rice straw, rape straw, corn straw, corn cob, rice husk or wheat straw.
3. The method for preparing straw-based broad-spectrum adsorption materials by mechanochemical green method according to claim 1 is characterized in that The particle size of the straw described in step 1 is 5 mesh to 800 mesh.
4. The method for preparing straw-based broad-spectrum adsorption materials by mechanochemical green method according to claim 1 is characterized in that The straw described in step 1 is pretreated straw, and the pretreatment is performed according to the following steps: washing and filtering with deionized water, and repeating the washing and filtering 1 to 5 times, and then vacuum drying at a temperature of 50° C. to 80° C. for 12 h to 24 h.
5. The method for preparing straw-based broad-spectrum adsorption materials by mechanochemical green method according to claim 1, characterized in that The molar ratio of the mass of the straw to phosphorus pentoxide described in step 1 is 4g:(3.5-7.1)mmol.
6. The method for preparing straw-based broad-spectrum adsorption materials by mechanochemical green method according to claim 1 is characterized in that The molar ratio of phosphorus pentoxide to N,N,N-trimethylglycine in step 1 is 1:(1-2).
7. The method for preparing straw-based broad-spectrum adsorption materials by mechanochemical green method according to claim 1, characterized in that The high-energy grinding described in step one is specifically carried out according to the following steps: using a planetary ball mill or a reciprocating mill, high-energy grinding for 1h to 12h at a vibration frequency of 15Hz to 30Hz and a ball-to-material mass ratio of (10 to 32):1; and changing the rotation direction of the ball mill once every 1h during the high-energy grinding process, using steel balls with a diameter of 5mm to 20mm as grinding balls.
8. The method for preparing straw-based broad-spectrum adsorption materials by mechanochemical green method according to claim 1, characterized in that The volume ratio of the crude product described in step 2 to deionized water is 1 g: (10-100) mL.
9. The method for preparing straw-based broad-spectrum adsorption materials by mechanochemical green method according to claim 1, characterized in that In step 2, the pH is adjusted to 2-14, and stirring is continued for 1 h to 12 h at a rotation speed of 100 rpm to 1000 rpm.
10. The method for preparing straw-based broad-spectrum adsorption materials by mechanochemical green method according to claim 1, characterized in that The centrifugal separation, drying and grinding into powder described in step 2 are specifically carried out according to the following steps: centrifugal separation at a rotation speed of 10000rpm to 13000rpm, then drying at a temperature of 50℃ to 80℃ for 12h to 24h, and finally manual grinding for 10min to 120min.